Fascia iliaca compartment block can reduce the incidence of early post-operative cognitive impairment in elderly patients with high-risk hip replacement - Tang, Li; Li, Bo; Guo, Shun; Zhao, Xiaoyong; He, Binbin; Liu, Weiwei; Xia, Rui (Frontiers in Aging Neuroscience, 2022)
Objective: In this study, we aimed to observe the effects of ultrasound-guided fascia iliaca compartment block (FICB) combined with hypobaric spinal anesthesia on postoperative pain and cognitive function in elderly high-risk hip-replacement patients. Methods: A total of 84 elderly patients, aged 65–85 years, with American Society of Anesthesiologists physical status III–IV, scheduled for hip arthroplasty between September 2021 and May 2022, were selected. One or more organs with moderate-to-severe impairment were included in all patients. Patients were randomly divided into a hypobaric spinal anesthesia group (group C, control group) and an ultrasound-guided FICB combined with hypobaric spinal anesthesia group (group E, experimental group). Group C used hypobaric 0.32% ropivacaine 3.5 mL spinal anesthesia and group E received ultrasound-guided FICB combined with hypobaric 0.32% ropivacaine 3.5 mL spinal anesthesia. Patients were compared using the visual analog scale (VAS) for pain, hip function (Harris), and simple Mini-Mental State Examination (MMSE) scale. Blood β-amyloid (Aβ) and neuronal microtubule-associated protein (tau) levels were measured. We compared intraoperative conditions and postoperative complications between the two groups to assess the effects of FICB combined with hypobaric spinal anesthesia on postoperative pain and cognitive function in elderly high-risk hip-replacement patients. Results: At 1 and 3 days after the operation, patients in group C had significantly higher VAS and lower MMES scores than those in group E. The differences were statistically significant at 1 day (P<0.01) and at 3 days (P<0.05) after the operation. At 1 day after operation, the Harris score of the patients in group C was significantly lower than that in group E (P<0.05). The Aβ and tau levels of patients in group C were significantly higher than those in group E at 1 day after the operation (P<0.01). The Aβ levels of patients in group C were significantly higher than those in group E at 3 days after the operation (P<0.05). The intraoperative conditions and complication rates did not differ significantly between the two groups. Conclusion: By lowering pain and managing Aβ and tau protein concentrations, FICB can successfully lower the incidence of early postoperative cognitive impairment in elderly high-risk hip-replacement patients.